2011
DOI: 10.1007/s11512-009-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

On the Lp-boundedness of pseudo-differential operators with non-regular symbols

Abstract: In this paper, we consider the continuity property of pseudo-differential operators with symbols whose Fourier transforms have compact support. As applications, we obtain the L p -boundedness for symbols in Besov spaces and in modulation spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Moreover, it might be worth mentioning that these values are partially sharp (see [26,Section 5]). Some results on this direction can be also found in, for instance, Boulkhemair [3], Coifman and Meyer [5], Cordes [6], Hwang [20], Muramatu [29], and Sugimoto [32] for p = 2 and Tomita [33] for 0 < p < ∞. For the multilinear case, in [21,22], it was shown that, for the case 2/N ≤ p ≤ 2 and 2 ≤ p 1 , .…”
Section: T Katomentioning
confidence: 78%
“…Moreover, it might be worth mentioning that these values are partially sharp (see [26,Section 5]). Some results on this direction can be also found in, for instance, Boulkhemair [3], Coifman and Meyer [5], Cordes [6], Hwang [20], Muramatu [29], and Sugimoto [32] for p = 2 and Tomita [33] for 0 < p < ∞. For the multilinear case, in [21,22], it was shown that, for the case 2/N ≤ p ≤ 2 and 2 ≤ p 1 , .…”
Section: T Katomentioning
confidence: 78%
“…ðℝ n × ℝ n Þ implies the L 2 -boundedness. Furthermore, Tomita [28] generalized the results in [27] and studied the L p -boundedness of pseudodifferential operators with non-regular symbols, where 1 < p < ∞. As some applications, Tomita [28] also obtained the L p -boundedness for symbols in Besov spaces and modulation spaces, respectively.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, Tomita [28] generalized the results in [27] and studied the L p -boundedness of pseudodifferential operators with non-regular symbols, where 1 < p < ∞. As some applications, Tomita [28] also obtained the L p -boundedness for symbols in Besov spaces and modulation spaces, respectively. Recently, the properties of multiparameter Besov-Lipschitz and Triebel-Lizorkin spaces and the boundedness of multi-parameter singular integral operators on them have been established in [29][30][31][32].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation